A Novel Non-Invasive Device for the Assessment of Central Venous Pressure in Hospital, Office and Home - Marcelli E (Dove Medical Press, 2021)
Emanuela Marcelli,1,* Laura Cercenelli,1,* Barbara Bortolani,1 Saverio Marini,2 Luca Arfilli,3 Alessandro Capucci,4 Gianni Plicchi5 1eDIMES Lab-Laboratory of Bioengineering, Department of Experimental, Diagnostic and Specialty Medicine (DIMES), Alma Mater Studiorum University of Bologna, Bologna, Italy; 2Ars Medica: Associazione Medico-Chirurgica Della Gallura, Olbia, Italy; 3Villa Laura Ospedale Privato Accreditato, Bologna, Italy; 4Abcardio Cardiological Center, Bologna, Italy; 5TRE ESSE Progettazione Biomedica S.r.l., Bologna, 40138, Italy*These authors contributed equally to this workCorrespondence: Laura CercenelliLaboratory of Bioengineering, Department of Experimental, Diagnostic and Specialty Medicine (DIMES), Alma Mater Studiorum University of Bologna, c/o S. Orsola Malpighi-Hospital, via Massarenti 9, Bologna, 40138, ItalyTel +39 0516364603Fax +39 0516364603Email laura.cercenelli@unibo.itBackground: Venous congestion can be quantified by central venous pressure (CVP) and its monitoring is crucial to understand and follow the hemodynamic status of patients with cardio-respiratory diseases. The standard technique for CVP measurement is invasive, requiring the insertion of a catheter into a jugular vein, with potential complications. On the other hand, the current non-invasive methods, mainly based on ultrasounds, remain operator-dependent and are unsuitable for use in the home environment. In this paper, we will introduce a novel, non-invasive device for the hospital, office and home assessment of CVP.Methods: After describing the measurement concept, we will report a preliminary experimental study enrolling 5 voluntary healthy subjects to evaluate the VenCoM measurements’ repeatability, and the system’s capability in measuring small elicited venous pressure variations (2 mmHg), as well as an induced venous hypertension within a pathological range (12÷ 20 mmHg).Results: The experimental measurements showed a repeatability of ± 1mmHg. The VenCoM device was able to reliably detect the elicited venous pressure variations and the simulated congestive status.Discussion and Conclusion: The proposed non-invasive VenCoM device is able to provide a fast and repeatable CVP estimate, having a wide spectrum of potential clinical applications, including the monitoring of venous congestion in heart failure patients and in subjects with renal and hepatic dysfunction, as well as pulmonary hypertension (PH) that can be extended to pneumonia COVID-19 patients even after recovery. The device needs to be tested further on a large sample size of both healthy and pathological subjects, to systematically validate its reliability and impact in clinical setting.Keywords: central venous pressure, pulmonary artery pressure, heart failure, non-invasive device, home monitoring, COVID-19, cardiovascular measurements